An efficient, bifunctional catalyst for lithium–oxygen batteries obtained through tuning the exterior Co2+/Co3+ ratio of CoOx on N-doped carbon nanofibers. Issue 8 (28th March 2019) - Zhang, Xiuling; Fan, Wei; Zhao, Shuyu; Cao, Ran; Li, Congju
Abstract : CoO x NPs@N-doped carbon nanofibers were obtained by an electrospinning technique and served as an excellent catalyst for Li–O2 cells. The enhanced electrochemical performance can be ascribed to the rich Co 2+ toward the ORR and OER on the surface of CoO x . Abstract : The design and fabrication of efficient catalysts are urgently desired for Li–O2 batteries to prompt both the oxygen reduction reaction and oxygen evolution reaction. Morphology/surface optimization can be intensively applied to enhance the catalytic activity of specific materials. Herein, we propose an electrospinning method followed by heat treatment to fabricate CoO x nanoparticles on N-doped carbon nanofibers (CoO x @NCF). Significantly, the electrocatalytic activity can be largely improved through modulating the exterior Co 2+ /Co 3+ ratio by controlling the heat-treatment process. The prepared CoO x nanoparticles possess high uniformity together with good dispersion, which integrates the advantages of morphology and surface properties, making them an effective active catalyst for Li–O2 batteries. The cell with the CoO x @NCF catalyst shows impressively good performance towards the ORR and OER with a high initial discharge capacity (7763.7 mA h g −1 ), enhanced cycling stability, desirable rate capability and relatively low overpotential. Moreover, the result of LSV indicates that CoO x @NCF enables the decomposition of the side product LiOH efficiently. In addition, the CoO x @NCF catalyst is capable of forming nanosheet-like Li2 O2, which is much easier to decompose, compared with toroidal-like Li2 O2 . The boosted cycling life can be attributed to the synergistic effect of architecture design and surface engineering.